Status, diversity and potential of semi arid indigenous and minor vegetables of western India - Yadav, Lalu Prasad; K., Gangadhara; Mishra, D. S.; Singh, Sanjay; Saroj, P. L. (Indian Horticulture, 2020)
Semi-arid indigenous and minor vegetables afford excellent opportunities for improvement of human health, and farmer’s household economic and social advancement. These vegetables are ideally suited to accomplish these objectives owing to their high economic and nutritive values and they can often serve as an engine for agricultural and economic diversification. Supplements and fortified foods can effectively address micronutrient deficiencies in the short-term, but food-based solutions, such as increasing the consumption of vegetables represent the most sustainable method of reducing and controlling micronutrient deficiencies in resource-poor communities. Supportive policies are needed to advance research, conservation, and documentation of neglected indigenous semi-arid vegetable species to protect and realize their role in nutrition-sensitive horticulture.